A chromosome‐level genome of Syringa oblata provides new insights into chromosome formation in Oleaceae and evolutionary history of lilacs. (14th July 2022) - Wang, Yi; Lu, Limin; Li, Jingrui; Li, Huayang; You, Yichen; Zang, Shuying; Zhang, Yongqing; Ye, Jianfei; Lv, Zemin; Zhang, Zhaoyu; Qin, Yongsheng; Zhang, Hongling; et al.
SUMMARY: Lilacs ( Syringa L.), a group of well‐known ornamental and aromatic woody plants, have long been used for gardening, essential oils and medicine purposes in East Asia and Europe. The lack of knowledge about the complete genome of Syringa not only hampers effort to better understand its evolutionary history, but also prevents genome‐based functional gene mining that can help in the variety improvement and medicine development. Here, a chromosome‐level genome of Syringa oblata is presented, which has a size of 1.12 Gb including 53 944 protein coding genes. Synteny analysis revealed that a recent duplication event and parallel evolution of two subgenomes formed the current karyotype. Evolutionary analysis, transcriptomics and metabolic profiling showed that segment and tandem duplications contributed to scent formation in the woody aromatic species. Moreover, phylogenetic analysis indicated that S. oblata shared a common ancestor with Osmanthus fragrans and Olea europaea approximately 27.61 million years ago (Mya). Biogeographic reconstruction based on a resequenced data set of 26 species suggested that Syringa originated in the northern part of East Asia during the Miocene (approximately 14.73 Mya) and that the five Syringa groups initially formed before the Late Miocene (approximately 9.97 Mya). Furthermore, multidirectional dispersals accompanied by gene introgression among Syringa species from Northern China during the Miocene were detected by biogeographic reconstruction. Taken together, the results showed that complex gene introgression, which occurred during speciation history, greatly contributed to Syringa diversity. Significance Statement: The construction of a high‐quality chromosome‐level genome of Syringa oblata combined with the analysis on chromosomes evolution, phylogenetic profiling and transcriptomics uncovers mechanisms of biogeographic dispersal routes and floral scent formation of lilacs Results presented here not only fill knowledge gaps on the evolution history of this temperate‐originated aromatic plant species from a biological and geographical perspective, but also provide bioinformatic tools that could improve its ornamental characteristics and explore medicinal functions.